A broad study on BRAC EPL stock brokerage limited : impact of commission rate on BRAC EPL stock brokerage Ltd. - Farina, Tasmin Jahan (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.